Aqueous two-phase system (ATPS): an overview and advances in its applications. Issue 1 (December 2016) - Iqbal, Mujahid; Tao, Yanfei; Xie, Shuyu; Zhu, Yufei; Chen, Dongmei; Wang, Xu; Huang, Lingli; Peng, Dapeng; Sattar, Adeel; Shabbir, Muhammad; Hussain, Hafiz; Ahmed, Saeed; et al.
Abstract Aqueous two-phase system (ATPS) is a liquid-liquid fractionation technique and has gained an interest because of great potential for the extraction, separation, purification and enrichment of proteins, membranes, viruses, enzymes, nucleic acids and other biomolecules both in industry and academia. Although, the partition behavior involved in the method is complex and difficult to predict. Current research shows that it has also been successfully used in the detection of veterinary drug residues in food, separation of precious metals, sewage treatment and a variety of other purposes. The ATPS is able to give high recovery yield and is easily to scale up. It is also very economic and environment friendly method. The aim of this review is to overview the basics of ATPS, optimization and its applications.